2018
DOI: 10.1186/s12931-018-0794-z
|View full text |Cite
|
Sign up to set email alerts
|

The aging lung: tissue telomere shortening in health and disease

Abstract: BackgroundTelomere shortening has been associated with several lung diseases. However, telomere length is generally measured in peripheral blood leucocytes rather than in lung tissue, where disease occurs. Consequently, telomere dynamics have not been established for the normal human lung nor for diseased lung tissue. We hypothesized an age- and disease-dependent shortening of lung tissue telomeres.MethodsAt time of (re-)transplantation or autopsy, 70 explant lungs were collected: from unused donors (normal, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 48 publications
2
30
1
Order By: Relevance
“…The finding provides rationale for further investigation of the association of lung telomere length and fibrosis in IPF lung. Telomere shortening is a hallmark of aging and just recently it was shown that, similar to other organs, telomeres in control lungs shorten with age [26]. However, lung telomere length in our IPF samples was shorter than in age-matched controls and did not correlate with age.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…The finding provides rationale for further investigation of the association of lung telomere length and fibrosis in IPF lung. Telomere shortening is a hallmark of aging and just recently it was shown that, similar to other organs, telomeres in control lungs shorten with age [26]. However, lung telomere length in our IPF samples was shorter than in age-matched controls and did not correlate with age.…”
Section: Discussioncontrasting
confidence: 67%
“…On HRCT, IPF lungs typically show an apicobasal gradient, in which fibrosis is most abundant subpleurally in the basal lung fields [1]. In control lungs, in which such a gradient is absent, it was recently found that telomere length in the basal fields was significantly shorter than in the apical fields of the same lung [26]. It is unknown whether telomere shortening in the IPF lung associates with the apicobasal gradient.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing senescent cell burden has been attributed to both IPF and COPD, with evidence from several cellular compartments including type II alveolar epithelium and fibroblasts (see [33] for a comprehensive review). Both IPF and COPD have significantly shorter leukocyte telomere length [5,6]; shortened telomeres have also been identified directly within lung tissue from IPF patients [8,34] but not in COPD [35]. In light of our findings, these observations suggest that telomere shortening can act as an intrinsic and systemic driving force of cellular senescence in IPF, akin to the relationship between telomere-associated driver mutations in familial PF.…”
Section: Discussionsupporting
confidence: 56%
“…A reduction in RTL was observed in peripheral lymphocytes in patients with COPD [57] and in lung epithelial cells exposed to cigarette smoke in vitro [58]. However, no significant difference in RTL was found in lung biopsies from patients with COPD compared to healthy controls [59], suggesting that these changes might be cell-type specific. Similarly, in T2D and atherosclerosis, RTL has been shown to be reduced in circulating leukocytes but with variable penetration across disease severity [60,61].…”
Section: Theme 1: Accelerated Ageing In Multimorbiditymentioning
confidence: 89%